Assessing Age as a Risk Factor for Complications in Autologous Breast Reconstruction. Issue 6 (December 2018) - Torabi, Radbeh; Stalder, Mark W.; Tessler, Oren; Bartow, Matthew J.; Lam, Jonathan; Patterson, Charles; Wise, M. Whitten; Dupin, Charles L.; St. Hilaire, Hugo
Abstract : Background: Breast cancer is primarily a diagnosis of older women. Many patients seeking breast reconstruction are elderly women (aged 65 years or older). However, many surgeons anecdotally believe that surgery in elderly patients is inherently dangerous, or at least prone to more complications. Methods: The authors conducted a retrospective cohort study composed of chart review of all deep inferior epigastric perforator flap breast reconstruction patients at a single institution divided into an elderly cohort (65 years or older) and a nonelderly cohort (younger than 65 years). Cohort was the primary predictor variable. Demographic and comorbidity data were secondary predictor variables. Primary outcomes were complete flap loss, partial flap loss, or need for flap reexploration. Secondary outcomes such as wound healing problems, seroma, and others were also assessed. Results: There were 285 flaps in the nonelderly cohort and 54 flaps in the elderly cohort. The elderly cohort had higher rates of diabetes, hypertension, and hyperlipidemia. Chi-square analysis showed no significant differences in primary outcomes between the two cohorts. Breast wound dehiscence was significantly higher in the elderly cohort ( p < 0.01). On logistic regression, being elderly was seen as a significant risk factor for complete flap loss (OR, 10.92; 95 percent CI, 0.97 to 122.67; p = 0.05). The overall success rate for the nonelderly cohort was 99.6 percent, whereas the success rate for the nonelderly cohort was 96.3 percent. Conclusions: Elderly women desire breast reconstruction. Free flap breast reconstruction is a viable and safe procedure in these patients. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, II.